Digital Money Literacy Education For Karang Taruna In Creating Technology Smart Human Resources In Villages - Nasution, Rizki Alfadilah; Widiasih, Suprapti; Prayitno, Hadi; Idyaningsih, Nining; Purnamasari, Eva (Universitas Pahlawan Tuanku Tambusai, 2024)
Community service activities through the digital money literacy education program for Karang Taruna aim to educate the community, especially Karang Taruna in Srimulyo Village, Dampit Regency, Malang, about the use of digital money transactions that have not been optimally used in realizing technologically intelligent human resources in the village. The implementation of the digital money literacy education program for Karang Taruna in Srimulyo Village was carried out on Wednesday, January 17, 2024. The results of this activity show that Karang Taruna in Srimulyo Village, Dampit Regency, Malang are educated and able to understand the need for technology in digital finance. The education provided explains how the use of digital money makes transactions easier in supporting the economy of the community in Srimulyo Village. The activity of using digital money transactions increases the ability of Karang Taruna in Srimulyo Village as technologically intelligent human resources. The use of applications in non-cash transactions can be an effective alternative in improving a safer payment system for Karang Taruna members and the local community.